Über Musik als Wirklichkeit - Feil, Arnold (Muzikološki zbornik, 2007)
The article discusses the relationship of music to reality as can be induced not only from theory but from the music itself and the listener's experience of it. The examples are taken from different historical contexts: Pater noster from the Roman Catholic Mass, Evangelic chanting practice, J. S. Bach's cantata and oratorio oeuvre, the philosophy of Heidegger, Hegel, and Nietzsche's perception of Wagner, Stravinsky and Stockhausen.
Keywords: funkcija; glasba; izkušnja; music; realnost; recepcija